Il passato nel presente: la lingua dei beni culturali - Farina, Annick; Funari, Fernando (Strumenti per la didattica e la ricerca, 2020)
As a sign, tangible heritage is the most visible trace of the past in our daily life. In constant dialectic with the intangible heritage, it constitutes a physical presence that forces us to take concrete awareness. Knowledge of texts and stories, which for Vitruvius is the high road for the design and construction of a building, is also fundamental in the processes of deconstruction, according to the various stages and different perceptions, through ages and customs, up to retrace the process that transformed it into 'heritage'. The lexicon and the terminology of cultural heritage are in this sense the most important vector of knowledge, enhancement and dissemination. The volume seeks to bring together those who study the language of heritage, from different countries and through different methodologies, and those involved in its management, in order to offer points of view and ideas on the narration and perception of tangible and intangible heritage, in mediation across eras, cultures and identities.